Linguistics an introduction - McGregor, William 1952- (Bloomsbury Academic, 2015)
"This is the new edition of Linguistics: An Introduction. It is a bestselling introductory textbook for all students of linguistics and language studies. This reworked edition features: [bullet] new chapters on sign languages, writing, and text and discourse. [bullet] coverage of writing in electronic media[bullet] revised and updated chapters on languages of the world and psycholinguisticsFirmly based around taught courses and catering to student needs, it addresses all the topics that a student will need in their initial and subsequent study of language. With key terms, further reading, questions at the end of each chapter, exercises and key paragraphs in stand-out boxes, this is a firmly pedagogic text that takes difficult concepts and explains them in an easy to understand way, with examples taken from a range of languages across the world. Global in its scope and comprehensive in its coverage, this is the textbook of choice for linguistics students. The book comes with a large Companion Website, also extensively revised and expanded, and, for lecturers and instructors, a comprehensive Answer Book is also available to go along with the questions throughout the chapters"--Provided by publisher.